Strategies for Developing Cycling Tourism in Mengesta Tourism Village - Wulandani, Ni Luh Kadek Laksmi; Kusuma Putra, I Made Rony Mulia; Septiani, Made Sera (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to formulate strategic directions for the development of cycling tourism based on natural and local cultural potential in Mengesta Village, Tabanan, Bali. The research seeks to identify and analyze the village’s internal strengths and weaknesses, as well as external opportunities and threats, in order to design sustainable and community-oriented tourism strategies. This research employs a qualitative descriptive approach. Data were collected through observations, interviews with local stakeholders (including Pokdarwis and community members), and document analysis. The analytical tool used is SWOT analysis, which systematically examines internal factors (strengths and weaknesses) and external factors (opportunities and threats). The results of the SWOT analysis are further synthesized into strategic formulations (SO, WO, ST, and WT strategies) to provide comprehensive development recommendations. The findings reveal that Mengesta Village has strong potential for cycling tourism development, supported by its scenic rural routes (±5–15 km), well-preserved agrarian environment, low traffic density, and the presence of the culturally significant subak system. However, several weaknesses were identified, including limited human resource capacity, lack of safety and service standards, inadequate supporting infrastructure, and suboptimal marketing strategies. Opportunities include the growing trend of cycling, wellness, and slow tourism, as well as increasing demand for environmentally friendly and authentic rural experiences. Meanwhile, threats consist of economic instability due to seasonal agriculture, competition with established destinations, and potential environmental degradation. The study concludes that Mengesta Village has significant potential to develop as a sustainable cycling tourism destination. By leveraging its natural and cultural assets while addressing existing limitations, the village can create competitive and resilient tourism products. The integration of sustainable tourism, community-based tourism, and asset-based development approaches ensures that tourism development not only enhances economic benefits but also preserves environmental quality and strengthens community participation in the long term.